Complex I syndrome in striatum and frontal cortex in a rat model of Parkinson disease - Valdez, Laura Batriz (2019)
Mitochondrial dysfunction named complex I syndrome was observed in striatum mitochondria of rotenone treated rats (2 mg rotenone/kg, i. p., for 30 or 60 days) in an animal model of Parkinson disease. After 60 days of rotenone treatment, the animals showed: (a) 6-fold increased bradykinesia and 60% decreased locomotor activity; (b) 35-34% decreases in striatum O 2 uptake and in state 3 mitochondrial respiration with malate-glutamate as substrate; (c) 43–57% diminished striatum complex I activity with 60–71% decreased striatum mitochondrial NOS activity, determined both as biochemical activity and as functional activity (by the NO inhibition of active respiration); (d) 34–40% increased rates of mitochondrial O 2 •- and H 2 O 2 productions and 36–46% increased contents of the products of phospholipid peroxidation and of protein oxidation; and (e) 24% decreased striatum mitochondrial content, likely associated to decreased NO-dependent mitochondrial biogenesis. Intermediate values were observed after 30 days of rotenone treatment. Frontal cortex tissue and mitochondria showed similar but less marked changes. Rotenone-treated rats showed mitochondrial complex I syndrome associated with cellular oxidative stress in the dopaminergic brain areas of striatum and frontal cortex, a fact that describes the high sensitivity of mitochondrial complex I to inactivation by oxidative reactions.